PCV2 load in preweaned piglets affected with porcine circovirus 2 associated diseases - SETHI, MENAKA; AGARWAL, SWATI; RAY, PRADEEP KUMAR; ANOOPRAJ, R; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2015)
Porcine circovirus associated diseases (PCVAD) caused by Porcine circovirus type 2 (PCV2) are responsible for heavy losses to the global swine industry in recent decades. PCV2 viral load varies significantly between diseased and subclinically infected pigs. Real time PCR is a highly sensitive technique enabling simultaneous amplification and quantification of specific nucleic acid sequences. Using this technique, the distribution and absolute quantification of PCV2 in naturally infected preweaned piglets was investigated. The viral load in different organs was in the range of (32.92×108 copies/μg DNA to 1.14×108 copies/μg DNA). Results indicate that in PCVAD affected preweaned pigs, lymphoid organs contain the highest viral loads, while intestine and brain the lowest viral loads. This preliminary data on virus load in the lymphoid organs of preweaned piglets will help differentiate mere PCV2 infection and clinical PCVAD.